The impact of Islamic financial development on renewable energy production in Islamic countries - Siswantoro; Mahmud, Amir (Asian Journal of Islamic Management (AJIM), 2023)
Purpose − This study aims to determine the impact of the development of Islamic finance on renewable energy production in Islamic countries. Two variables representing Islamic finance (Islamic financing and Sukuk) and five control variables (economic growth, foreign investment, CO2 emissions, trade openness, and consumer price index) are also studied.Methodology − Ninety-panel data from 10 Islamic countries over a period of 9 years (2013-2021) were analyzed using panel data analysis with the fixed effect model approach.Findings − The results show that Islamic countries with good development of Islamic banking and Sukuk tend to experience an increase in renewable energy production. Other empirical findings show that economic growth, CO2 emissions, and consumer price index are the next variables that affect renewable energy in Islamic countries.Implications − The results of this study have implications for the policies of Muslim countries to further encourage Islamic finance to be channeled into the renewable energy sector. The government should establish a clear regulatory framework for green Islamic investment and financing and if necessary, they are needed to provide incentives to the green investment sector.Originality − Previous studies that directly examine the effect of Islamic financial development on renewable energy are still limited. Most of the previous studies have examined the impact of Islamic financial development on environmental issues such as sustainable development, climate change, or environmental quality